Efeito do dry neendlig na dor muscular de início tardio em mulheres saudáveis: ensaio controlado randomizado e cego - Viana, Joelmir Lisboa (2024)
Introduction: Delayed Onset Muscle Soreness (DOMS) likely occurs due to unfamiliar exercises or excessive sets or loads. Strategies to accelerate recovery should be implemented so that the individual can return to performing exercises efficiently as soon as possible. In the scientific and clinical field, the use of Dry Needling (DN) has gained prominence, although its effects on DOMS are still underexplored. Objective: To investigate the effect of DN on DOMS administered immediately after an eccentric exercise protocol on the biceps brachii in healthy women. Methods: This is a randomized, controlled, and blinded clinical trial, composed of forty women. All participants were initially assessed with measurements of pain perception (numerical pain scale and algometry), dynamometry, and treatment expectations. They then performed an exercise protocol on an isokinetic dynamometer, consisting of 2 sets of 6 eccentric contractions at 60°/s for the elbow flexors. After the protocol, participants received an intervention according to the group to which they were randomly assigned: the DN group, where dry needling was applied, and the sham group (SG), where needle penetration was simulated. Finally, re-evaluations were conducted immediately and 48 hours after the intervention protocol, except for the Numerical Pain Scale (NPS), which was also assessed at 24 and 72 hours post-exercise. The analysis focused on pain perception (NPS and pain threshold), peak torque normalized by body weight, average peak torque, power, and work. Statistical analysis included Kolmogorov-Smirnov and Levene tests and mixed ANOVA. The Bonferroni post-hoc test was applied to identify differences when a significant F value was found. Statistical significance was set at 5% with a 95% confidence interval. Results: No significant differences were observed between the groups for pain sensation at any time point. No differences were found between groups for the other secondary outcomes. Conclusion: Dry needling treatment was not effective in reducing pain sensation, pain threshold, or muscle performance in the participants.